“Let Them Stay There”: COVID-19 and Zimbabwe’s Indignation Against Return Migrants and Travelers - Hungwe, Chipo; Mugari, Zvenyika (African Human Mobility Review, 2024)
This paper explains the indignation against and stigmatization of return migrants and travelers when Zimbabwe first recorded cases of COVID-19 in 2020. While xenophobic hatred toward foreign migrants enjoyed much media and scholarly attention, the similar risk faced by the return migrants and travelers among “their own” during the pandemic was largely left on the back burner. The paper uses secondary analysis of information from social media, government reports, media briefings, and public utterances of government officials to provide an explanation for the negative attitudes of locals against migrants at the height of COVID-19. The findings revealed that in times of change and dealing with uncertainty, there is a tendency to redraw boundary lines between in-groups and out-groups with negative consequences for those labeled as the out-group. For some time, the returnees were stigmatized as harbingers of the COVID-19 virus and viewed as troublesome and acting in an unreasonable manner, thus courting the indignation of local Zimbabweans. This paper lends support to the view that pandemics create fear, which results in the rejection and exclusion of ordinary members of the in-group. Perceived resource competition, resource scarcity, anxiety, and fear heightened the stigmatization of return migrants and travelers. To build back better from the negative effects of the pandemic, there is a need to review COVID-19 preventive measures, avoid reckless public pronouncements that stigmatize and stoke hatred for return migrants, and invest in the healthcare system.